2001
DOI: 10.1046/j.1365-2133.2001.04492.x
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-induced linear IgA disease with autoantibodies to BP180 and LAD285.

Abstract: Linear IgA disease (LAD) is an acquired autoimmune subepidermal bullous disease characterized by the linear deposition of IgA at the basement membrane zone. A minority of cases are induced by drugs, of which the most frequently implicated is vancomycin. The target antigens in idiopathic LAD are heterogeneous, but have not previously been reported in vancomycin-induced LAD. We report three cases, and in two of these we investigated the target antigens. In both we identified IgA antibodies to LAD285 and IgA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 39 publications
(62 reference statements)
1
59
0
1
Order By: Relevance
“…In the case of druginduced LABD, there are far fewer cases that have been reported, and thus it has been harder to characterize the target antigen involved. Two studies have found antibodies to the 230kD antigen, the 97kD antigen, and type-VII collagen in nonvancomycin drug-induced LABD 14,15 , and one study reported two patients with vancomycin-induced LABD with autoantibodies against BP180 and LAD 285 10 . The severity of the reaction does not appear to correlate with serum vancomycin levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of druginduced LABD, there are far fewer cases that have been reported, and thus it has been harder to characterize the target antigen involved. Two studies have found antibodies to the 230kD antigen, the 97kD antigen, and type-VII collagen in nonvancomycin drug-induced LABD 14,15 , and one study reported two patients with vancomycin-induced LABD with autoantibodies against BP180 and LAD 285 10 . The severity of the reaction does not appear to correlate with serum vancomycin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Several drugs have been implicated as the cause of LABD, vancomycin being the most frequent [6][7][8][9][10][11][12] . LABD can occur anytime from 1 day to 1 month following the initial administration of vancomycin 10 . In addition to the usual vesiculobullous presentation, vancomycin-induced LABD can also appear as erythematous papules, erosions, urticarial lesions, and eczematous patches 9 .…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] The male-female ratio was 1:1, and the age ranged from 32 to 92 years with a mean of 64.7 years (SD: 14.6; 95% CI: 58.6-70.9). Vancomycin turned out to be the most incriminated drug capable of inducing disease when compared with each single drug, that is, captopril (OR: 14; 95% CI: 3.86-50.72; P \ .0001) and, to a lesser extent, even with all drugs overall (OR: 0.73; 95% CI: 0.33-1.59; P = .55).…”
Section: Suspected Offending Drugs Latency Period and Concurrent Mementioning
confidence: 99%
“…In total, 52 patients with LAD were described: 28 (53.8%) induced by medications other than vancomycin 7-32 and 24 (46.2%) by vancomycin. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] All demographic characteristics and immunohistopathological assessments are summarized in Table II.…”
Section: Demographics Immunohistopathological Assessment and Clinicmentioning
confidence: 99%
“…Linear IgA disease (LAD) can be drug-induced, and affected patients have IgA antibodies to bullous-pemphigoid-associated antigen 1 (BPAG or BP1) or other antigens (Palmer et al, 2001). LAD is especially commonly induced by vancomycin (Kuechle et al, 1994), but other drugs such as angiotensin-converting enzyme inhibitors may be involved (Femiano et al, 2003).…”
Section: (F) Drug-related Pemphigoid-like Reactions and Other Bullousmentioning
confidence: 99%